Skrining Psikologis Tumbuh Kembang Anak sebagai Upaya Mewujudkan Generasi Tangguh Demi Ketahanan Nasional - Afini Freudwi Asri; Dita Mediasari; Linda Ernawati; Rachmat Taufiq (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This community service activity aimed to conduct psychological screening of children’s growth and development and to enhance parents’ capacity in understanding their children’s psychological development. The program was organized by the Faculty of Psychology, Universitas Jenderal Achmad Yani, in collaboration with the Karsa Media Bakti Foundation (YKMB), and was participated in by 19 children and their parents residing in Cimahi and Bandung. The activity consisted of four stages: completion of screening forms and developmental history by parents, structured interviews and anamnesis, observation and brief individual counseling, and evaluation of participants’ knowledge and satisfaction. Data were analyzed using descriptive qualitative and simple quantitative approaches. The results showed that the most common problems included emotional regulation difficulties (31.6%), learning focus issues (26.3%), and social behavior problems (15.8%). Parents’ knowledge increased by an average of 36%, and the overall satisfaction level reached 4.7 out of 5. This program demonstrates that community-based psychological screening involving active participation of children and parents is an effective preventive approach for early detection of developmental issues. It is recommended that similar programs be conducted regularly and expanded to schools and other communities to strengthen family roles in building resilient generations for national endurance.